Mesoporous generation-inspired ultrahigh capacitive deionization performance by sono-assembled activated carbon/inter-connected graphene network architecture. (1st July 2016) - Song, Haiou; Wu, Yifan; Zhang, Shupeng; Li, Wentao; Wang, Baijun; Wang, Changming; Gao, Juanjuan; Li, Aimin
Graphical abstract: Highlights: 3D AC/inter-connected graphene network architecture has been constructed for CDI application. Generated mesoporous structures can inspire ultrahigh capacitive deionization performance. Usage of the smaller amounts (5 wt%) of functionalized graphene reduce the secondary pollution. Inter-connected graphene network as the conductive bridge can decrease the aggregation of AC. The environmental and economical composite electrode is suitable for practical CDI application. Abstract: Capacitive deionization (CDI) is an emerging technology that supplies deionized water to resolve the fresh water shortage. CDI electrodes are mainly made up of carbon materials, of which the deionization performance is closely related to their physical properties and structures. Hence, a rational design of electrode material structure is essentially significant. Functionalized graphene (fG) in particular has recently been regarded as characteristic CDI electrode material. However, preparation of fG based on graphene oxide usually results in serious secondary pollution due to usage of highly poisonous chemicals, and thus still cannot meet the demand of practical application. It is feasible that environmentally-friendly activated carbon (AC) and small amounts of fGs can be combined rationally, and used as CDI electrodes. Here, sono-assembled AC/m-phenylenediamine (mPEA) or p-phenylenediaminefG inter-connected network architecture has been constructed for the first time successfully. The specific capacitances of the AC/fG composites were found to be significantly higher than that of the AC electrode owing to mesoporous generation. Also, among all the samples, the AC composite with 5 wt % mPEA-fG exhibited an ultrahigh electrosorption capacity of 12.58 mg/g (or 0.22 mmol/g) in NaCl solution. These observations indicate that fG can serve as an efficient conductive bridge to decrease the aggregation of AC particles, and improve the electron transfer with the composite electrode. This work provides an effective strategy for the environmental and economical electrode architectures for general applications in CDI and energy storage.